THE DETECTOR METHODS OF COLOR CHANGING TO NON-INVASIVE AND ECONOMICAL NANOFILLER COMPOSITE RESIN BASED ON OPTICAL IMAGING - Apsari, Retna; Yhun Yhuana, Yhosep Gita; Listya Rhomdoni, Ardan; Na'imah, Syahidatun; Constella Anastasya Firdauz, Grace (Faculty of Advanced Technology and Multidiscipline Universitas Airlangga, 2024)
It has been developed the detector method of color changing to non-invasive and economical nanofiller composite resin based on optical imaging. The method is chosen due to the easiness of information in images form to be understood. The color changing is represented by the changing of brightness intensity laser which transmitted by samples. The light source uses green pointer laser with 532 nm of wavelength of and webcam sensor which can be obtained in the local market. Fraunhofer diffraction principle is used to utilize set up and test material treatment. By utilizing IC LM 317, it is made a series of regulators so that the laser pointer can be the input voltage from voltage source (AC). The light source of laser pointer is exposed to the test materials for detecting the intensity of transmission. Samples are made as thin as possible in order to transmit light and are given treatment in form of immersion in tea and coffee solution. Immersion is done for 1 week for 4 hours per day. The transmission intensity of samples captured by webcam and processed using the Delphi program. The data collections in form of transmission intensity are in pixel scale. The results indicate that the longer time immersion used affect the transmission intensity of samples decrease. These results can be seen from graph of the relation between transmission intensity with longer time of immersion. This detector can be used to help characterization of color's stability determination on the material which is portable gear.